IMPLEMENTASI METODE CERTAINTY FACTOR DALAM SISTEM PAKAR DIAGNOSIS PENYAKIT PARU-PARU BERBASIS ANDROID - , Syamsul Bahri, Muhammad Iqbal , Fatma Agus Setyaningsih (Universitas Tanjungpura, 2019)
The human lungs are organs that are susceptible to disease. The high risk of death of lung disease patients shows that this type of disease needs to be taken seriously. This is due to a lack of public knowledge and awareness about lung health. The immense number of lung disease sufferers is inversely proportional to the availability of pulmonogists, in Pontianak City alone in 2016 only had 3 pulmonologists.To overcome these problems, in this study an expert system was built using the Certainty Factor method. The process of calculating Certainty Factor uses the trust value given by experts and also the user to produce a diagnosis of the disease, each symptom has an MB and MD value for a disease given by an expert to determine the results of a system diagnosis based on symptoms felt by the user. The CF method has a system performance that is able to run according to functional requirements and results in a high accuracy percentage.The expert system that has been built in this study is based on Android, by calculation based on the results of testing, all expert system functionality in diagnosing lung disease goes according to system requirements, and has an accuracy rate of 85.18%. of 27 test data.Keywords: Lung Disease, Expert System, Certainty Factor, Android.